The Prevalence of Polio Vaccination Hesitancy and its Contributing Factors in Garah Tajik and Nahaqi, Peshawar - Abdullah, Khadija Nowaira; Shah, Farhan Anwar; Ahmed, Shahkar; Abid, Zalanda; Zia, Safoora; Mehmood, Saba; Nayab, Aimen; Fareed, Ibad; Khan, Talha (Journal of Postgraduate Medical Institute, 2026)
Abstract Objective: To estimate the prevalence of Polio vaccine hesitancy and to identify associated factors among parents in the remote areas of Garah Tajik and Nahaqi, District Peshawar. Methodology: A cross-sectional study was conducted from May to September 2024 at Emergency Satellite Hospital Nahaqi and Category D Hospital, Garah Tajik, using non-probability convenience sampling. A total of 200 parents of children under five participated in the study. Data were gathered through a structured questionnaire adapted from the WHO SAGE Vaccination Hesitancy Tool, capturing demographic information, attitudes toward polio vaccination, and perceived barriers to vaccination. Data were analysed using SPSS version 26.0 for frequencies and associations. Results: Among the 200 participants, 15 % (30) reported hesitancy toward polio vaccination. Key factors associated with hesitancy included social pressure from local community members (9.5%, n=19), fear of vaccine side effects (8%, n=16), and concerns about the vaccine’s effectiveness (5%, n=10). 68.5% (137) of participants were from low-income households and 56.5% (113) of mothers lacked formal education, underscoring socioeconomic challenges as contributors to vaccine hesitancy. Notably, 70.5% (141) of participants cited support from religious leaders as a positive influence on vaccination decisions. There was significant association between education level of fathers and vaccine hesitancy (p = 0.003). Conclusions: Polio vaccine hesitancy in Garah Tajik and Nahaqi is influenced by a combination of social, cultural, and economic factors. Community support, especially from religious leaders, appears to mitigate hesitancy, highlighting a potential intervention point. Addressing misinformation, improving healthcare access, and engaging local leaders are essential strategies to increase vaccine acceptance and contribute to eradication efforts. Key words: Polio, Vaccine hesitancy, Pakistan